Summer : A Solstice Story - Gross, Kelsey Ebben, 1982-; Liwska, Renata (New York : Simon & Schuster Books for Young Readers, 2024)
Owl and friends are gathering up gifts of love from the woodlands to honor the shining spirits of new life on the longest day of the year.
Keywords: Summer solstice -- Juvenile fiction; Owls -- Juvenile fiction; Forest animals -- Juvenile fiction; Summer solstice -- Fiction; Owls -- Fiction; Forest animals -- Fiction; Picture books; Animal fiction; Picture books